2021
DOI: 10.1073/pnas.2022578118
|View full text |Cite
|
Sign up to set email alerts
|

Virus-induced cell gigantism and asymmetric cell division in archaea

Abstract: Archaeal viruses represent one of the most mysterious parts of the global virosphere, with many virus groups sharing no evolutionary relationship to viruses of bacteria or eukaryotes. How these viruses interact with their hosts remains largely unexplored. Here we show that nonlytic lemon-shaped virus STSV2 interferes with the cell cycle control of its host, hyperthermophilic and acidophilic archaeon Sulfolobus islandicus, arresting the cell cycle in the S phase. STSV2 infection leads to transcriptional repress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 84 publications
2
55
0
1
Order By: Relevance
“…The DNA content distributions of the CK culture were also similar to those before the transfer, indicating that SMV1 maintains a stable infectious status in the cells instead of inducing cell lysis, in line with previous studies on SMV1 and other Sulfolobus viruses (Guo et al, 2019;Liu et al, 2021a;Prangishvili et al, 2006;Uldahl et al, 2016).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The DNA content distributions of the CK culture were also similar to those before the transfer, indicating that SMV1 maintains a stable infectious status in the cells instead of inducing cell lysis, in line with previous studies on SMV1 and other Sulfolobus viruses (Guo et al, 2019;Liu et al, 2021a;Prangishvili et al, 2006;Uldahl et al, 2016).…”
Section: Resultssupporting
confidence: 87%
“…Furthermore, infected Ago-1-2 cells were depleted of DNA at 24 hpi, whereas the SMV1-infected CK cells showed a similar DNA content distribution to uninfected cells (Figure 1F). At 48 hpi, a fraction of the infected CK cells had lost their genomic DNA, while a larger fraction contained more DNA than uninfected cells, suggesting an accumulation of viral DNA and/or suppression of cell division (Guo et al, 2019; Liu et al, 2021a). Finally, SYTO9/PI staining indicated that most infected Ago-1-2 cells lost membrane integrity at 72 hpi, in contrast to the much smaller fraction of infected CK cells and in line with the DNA content distribution analysis (Figure 1G).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, virion morphogenesis and egress of the archaeal lemon-shaped fusellovirus SSV1 are concomitant and occur at the cellular cytoplasmic membrane via a mechanism highly reminiscent of the budding of enveloped eukaryotic viruses (7). Similarly, archaeal pleolipoviruses and bicaudaviruses have been proposed to use budding as an exit mechanism (13,55). Hence, the finding that SIFV virions are enveloped inside the cell cytoplasm was unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have provided first insights into different steps of the infection cycle for several model archaeal viruses, showing that some of the mechanisms used by archaeal viruses to interact with the hosts are similar to those of eukaryotic and/or bacterial viruses, whereas others are unique (6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Many viruses are known to manipulate the cell cycle to ensure the most favorable intracellular conditions for virus replication ( Bagga and Bouchard, 2014 ; Fan et al, 2018 ; Liu J. et al, 2021 ). Interestingly, clandestinovirus encodes two cyclins with homologs in giant viruses and herpesviruses.…”
Section: Discussionmentioning
confidence: 99%